2023
DOI: 10.1002/hyp.14893
|View full text |Cite
|
Sign up to set email alerts
|

Model‐coupled GRACE‐based analysis of hydrological dynamics of drying Lake Urmia and its basin

Abstract: Lake Urmia basin (LUB), in northwestern Iran, is under the influence of extreme degradation due to a number of natural and anthropogenic factors. The existence of the Lake is critical for the microclimate of the region as well as the quality of human life and wildlife, which necessitates an up-to-date and holistic analysis of its hydrological dynamics. In this premise, satellite-based terrestrial water storage (TWS) received from the Gravity Recovery and Climate Experiment (GRACE) mission was coupled with hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…These metrics indicated a strong agreement between the predicted and observed GRACE TWSA values, affirming the reliability of the trained STL model. Previous studies have also shown the effectiveness of the STL method in reconstructing TWSA data (Ali, Ran, Luan, et al, 2024;Khorrami, Ali, Sahin, & Gunduz, 2023). The trained STL model was further applied to reconstruct TWSA between GRACE and GRACE-FO mission for all months with missing data (Figure S4b in Supporting Information S1).…”
Section: Gap-filled Results For Bridging Twsa Between Grace and Grace-fomentioning
confidence: 99%
See 1 more Smart Citation
“…These metrics indicated a strong agreement between the predicted and observed GRACE TWSA values, affirming the reliability of the trained STL model. Previous studies have also shown the effectiveness of the STL method in reconstructing TWSA data (Ali, Ran, Luan, et al, 2024;Khorrami, Ali, Sahin, & Gunduz, 2023). The trained STL model was further applied to reconstruct TWSA between GRACE and GRACE-FO mission for all months with missing data (Figure S4b in Supporting Information S1).…”
Section: Gap-filled Results For Bridging Twsa Between Grace and Grace-fomentioning
confidence: 99%
“…The Seasonal Trend Loess (STL) method (Cleveland et al., 1990) was used to reconstruct the TWS anomalies for the missing months. The STL approach was chosen because of its simplicity, computational efficiency, and documented reliability in previous studies (Ali, Ran, Luan, et al., 2024; Khorrami, Ali, Sahin, & Gunduz, 2023). STL was applied on the monthly time series of each GRACE grid, decomposing it into trends, seasonality, and residuals as follows: TWSt=Tt+St+Rt ${\text{TWS}}_{t}={T}_{t}+{S}_{t}+{R}_{t}$ where TWS, T , S , and R represent the original TWS, trend, seasonality, and residuals at time t , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the inflow of water into the lake has decreased 26 . Thus, the alarming shrinkage of the lake can be attributed to a combination of climatic extremes and anthropogenic activities, along with unsustainable water management 27 . To address the environmental tragedy of the LU, the Lake Urmia Restoration Program (ULRP) was initiated in 2013 as a ten-year program.…”
Section: Introductionmentioning
confidence: 99%
“…The GRACE observations have so far been applied for the largescale assessment of water storage, groundwater storage, and drought (e.g., Abhishek, 2022;Ali et al, 2023;Guo et al, 2021;Khorrami, Ali, Sahin, & Gunduz, 2023;Khorrami & Gunduz, 2021a;Khorrami & Gündüz, 2022;Li et al, 2019;Liu, Pei, & Shen, 2022;Tariq et al, 2023;Wang et al, 2020;Wang et al, 2022;Zhao et al, 2022). The GRACE-based drought indicators such as total storage deficit index (TSDI) (Yirdaw et al, 2008), water storage deficit (WSD) (Thomas et al, 2014), GRACE-based hydrological drought index (GHDI) (Yi & Wen, 2016), GRACE-drought severity index (GDSI) , Water Storage Deficit Index (WSDI) (Sinha et al, 2017), Modified Total Storage Deficit Index (MTSDI) (Hosseini-Moghari et al, 2019), combined climatologic deviation index (CCDI) (Sinha et al, 2019), and enhanced water storage deficit index (EWSDI) (Khorrami & Gunduz, 2021a) have been developed and used worldwide.…”
mentioning
confidence: 99%